Analisis Kematangan Tata Kelola Teknologi Informasi Pada Proses Pengendalian Internal Menggunakan Framework COBIT 5 (Studi Pada IT / FMS Department PT. Macmahon Mining Service Batang Toru) - Bernardus Alexander Habeahan; Andi Reza Perdanakusuma; Widhi Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Macmahon Mining Service Batang Toru maintains the quality of telecommunications services and fleet management through the activities of Fleet Management System by IT / FMS Department. Based on the results of interviews with FMS Senior Engineer, said that the FMS department governance had never been evaluated, FMS activities had not all been documented in a company document, lack of SOPs that discussed actions in dealing with problems, and inability of FMS departments to assist services and assessment quickly in the field. Capability analysis of IT governance in the internal control process using the COBIT 5 framework will produce an overview of the current level of IT governance capabilities and recommendations for future improvements. The first step is doing data collection through questionnaires to selected respondents based on the RACI Chart, then conducted observations, interviews, and documentation. Then conducting a self-assessment process that resulted in the capability level of IT governance in the internal control of IT / FMS department is at level 1 at 84%. Furthermore, doing a gap analysis, where the target level is 2 so as to produce a gap is 1. The last stage is to prepare recommendations for improvement that focus on planning and making standard internal control documents, comparing results of performance with other departments, documenting every main risk and nom-main risk, and increase the number of personnel.